Pengaruh Metode Pembelajaran Two Stay Two Stray (TSTS) Terhadap Peningkatan Hasil Belajar Pendidikan Agama Islam Kelas XI SMA Muhammadiyah 9 Brondong Lamongan - Nur Alfiani Putri Maftuhah (Jurnal Mahasiswa Pendidikan, 2021)
The purpose of this study is to analyze whether there is an effect of the Two Stay Two Stray learning method on improving Islamic Religious Education learning outcomes at SMA Muhammadiyah 9 Brondong. The type of research used is quantitative research with parametric statistical tests. The location of the research was carried out at SMA Muhammadiyah 9 Brondong. The population in this study were all students of class XI who found 145 people with 36 samples taken randomly. Data collection techniques in this study using observation, documentation, and tests. The data analysis technique used is t-test. Based on the test results using the significance test (t-test) obtained tcount of 6.652, then compared with ttable for a significant level of 5% (0.05) using a two-party test with dk = n-2 = 34, then obtained ttable of 2.032. With this it is known that tcount (6.652) > ttable (2.032), then H0 is rejected and Ha is accepted. It can be said that the Two Stray Two Stray learning method has a significant influence on improving Islamic Religious Education (PAI) learning outcomes for class XI SMA Muhammadiyah 9 Brondong for the 2021/2022 school year.